Safekeeping of tools in Goffin's cockatoos, Cacatua goffiniana. (June 2017) - Auersperg, A.M.I.; Köck, C.; Pledermann, A.; O'Hara, M.; Huber, L.
Abstract : Tool use in animals can be costly as foraging tools need to be actively searched for or manufactured. Consequently, some habitually tool-using species keep their tools safe and 'recycle' them for further use. We tested the Indonesian Goffin's cockatoo, a parrot with the capacity but no apparent adaptive specialization for tool use to investigate how tool safekeeping can arise innovatively. In this case, we further intended to test whether and how such safekeeping changes in different feeding contexts. We demonstrate that, in a set-up allowing for tool losses, the birds quickly started to keep their tools safe in between tool-using events. They used different individual strategies, suggesting that the behaviour was a product of innovation rather than inherited predispositions. The frequency of safekeeping improved over time indicating individual learning. Furthermore, the birds flexibly adjusted their performance depending on different contexts: paralleling previous results in the habitually tool-using New Caledonian crow, Corvus moneduloides, the cockatoos saved their tools more often when the foraging site was elevated and when the food item was easy rather than difficult to process. Furthermore, when feeding at heights, the birds tended to use a different safekeeping mode than when the foraging site was low. Highlights: Nonspecialized tool-using Goffin's cockatoos show safekeeping of tools for later use. Safekeeping of tools was achieved through individual learning. The frequency and mode of safekeeping are context dependent. Safekeeping patterns paralleled those of specialist tool-user, New Caledonian crow.